PEMUPUKAN N, P, DAN K SPESIFIK LOKASI PADA TANAMAN JAGUNG - nFN Syafruddin (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2016)
ABSTRACT Fertilizer Recommendation of N, P and K Site-Spesific Location for Maize Cropping in Gowa District, South Sulawesi. Agroecosystem of maize cropping areas in Indonesia is very varied. Site-specific fertilization can improve efficiency and productivity, increase farmer’s income and support sustainability of production system, environmental safety as well as saving energy resources. This research aimed to obtain fertilizer recommendation of N, P, and K for maize in specific location based on agro-ecosystem cropping areas. The research was carried out in Gowa district, South Sulawesi from March to September 2012. A survey method was used to collect data using questions in Nutrient Expert (NE) program forms. Average yield productivity of farmers’ field, yield potential or highest yield, physical and chemical properties of soil, crop management, fertilizers application at each maize cropping area were grouped and simulated using NE program to determine fertilizer dosage. Dosage obtained through NE simulation program then was used to analyze Marginal Rate of Return (MRR). Simulation results were feasible as recommended fertilizer if value of MRR >100%. Results of this research showed that site-specific fertilizer recommendation for maize in lowland of Gowa District were 190-210 kg N, 30-66 kg P2O5, and 33-55 kg K2O per hectare with MRR value at 180-479%, which could increase yield up to 3.3 t/ha; whilst on dryland,the dosage of N, P2O5 and K2O were 90-170 kg, 47-57 kg, 33-63 kg per hectare, respectively with MRR value 180-407%. It increased yield up to 2.7 t/ha. Although the fertilizer recommendations had a higher cost than existing fertilizer application at the farmers level, the gross revenue, income and RC ratio were higher than existing fertilizer application both in lowland and dryland. Recommended fertilizer dosages were able to decrease N fertilizer application in lowland up to 32.3 kg/ha, and on dryland 34.3 kg/ha. However, it also caused the increasing of P application by 35.7 kg and 36.4 kg K2O in lowland, whereas in dryland up to 31.5 kg P2O5/ha and 38.5 kg K2O. The recommendation of site specific fertilizer application is very useful and beneficial to increase maize productivity. Keywords: fertilization, site-specific, cornABSTRAKAgroekosistem pengembangan jagung di Indonesia sangat beragam. Pemupukan spesifik lokasi dapat meningkatkan efisiensi pemupukan, produktivitas, pendapatan petani, mendukung keberlanjutan sistem produksi, kelestarian lingkungan, dan penghematan sumberdaya energi. Penelitian ini bertujuan mendapatkan rekomendasipemupukan N, P, dan K spesifik lokasi pada tanaman jagung berdasarkan agroekosistem lahan. Penelitian dilaksanakan di Kabupaten Gowa, Sulawesi Selatan Maret sampai September 2012. Metode survei digunakan dalam penelitian ini. Data dikumpulkan berdasarkan pertanyaan pada isian program Nutrient Expert (NE). Data rata-rataproduktivitas yang diperoleh petani, potensi hasil atau hasil tertinggi yang pernah dicapai, sifat fisik dan kimia tanah,pengelolaan tanaman, pemupukan pada masing-masing sentra pertanaman jagung dikelompokkan dan disimulasikanmenggunakan program NE untuk menentukan takaran pupuk. Marginal Rate of Return (MRR) selanjutnya dianalisis